Validation of antinflammatory, antinociceptive and diuretic potential of neeraral (Marsilea quadrifolia L.) - Neethu Viswan (Department of Plant Biotechnology, College of Agriculture, 2017)
This thesis research programme entitled “Validation of anti-inflammatory, antinociceptive and diuretic potential of neeraral (Marsilea quadrifolia L.)” was carried out in the Ethnomedicine and Ethnopharmacology Division of Jawaharlal Nehru Tropical Botanic Garden and Research Institute (JNTBGRI), Palode, Thiruvananthapuram during the academic year 2016-2017. The objective of the study was to scientifically validate the traditional claims of neeraral (Marsilea quadrifolia L.) for its anti-inflammatory, antinociceptive and diuretic effects in experimental animal models. Neeraral (Marsilea quadrifolia L.) is a pteridophyte which is mostly aquatic and seen in marshy or swamp places. The plant material for the study was collected from a marshy land in Alappuzha district and were maintained at JNTBGRI to conduct the pharmacological studies. Extraction procedures were carried out to prepare drugs of various doses for these studies. Acute oral toxicity studies in mice, anti-inflammatory studies in rats, antinociceptive studies in mice and diuretic studies in rats were done as pharmacological analysis. Toxicity studies were investigated in Swiss albino mice for 14 days by the administration of 4 doses of the ethanolic extract of Marsilea quadrifolia (EMQ) i.e., 5, 50, 300 and 2000 mg/kg body weight and the animals showed no symptoms of toxicity even up to the highest dose. Antiinflammatory effect of EMQ was validated by carrageenan induced paw oedema and formalin induced paw oedema. The maximum percentage inhibition of paw oedema was shown by EMQ 450 (mg/kg) followed by EMQ (150 mg/kg). Antinociception studies were analyzed by two methods namely hot plate test and acetic acid induced writhing test in mice, which were appropriate for determining central and peripheral analgesic activities respectively. There was a significant effect with the drug doses of EMQ at 150 and 450 mg/kg compared to the reference drug aspirin. The diuretic effect of the EMQ were assessed by the parameters such as urine volume, Na+, K+ and Cl- concentrations by acute and sub-chronic methods. Both methods showed an increase in these parameters in a dose dependent manner which is comparable with the standard drug furosemide. The EMQ (150 mg/kg) was found to significantly exhibit antiinflammatory, antinociceptive and diuretic effect in all the in vivo experiments conducted and thus it can be considered as the effective dose.